Pengaruh Pemberian Kulit Ari Biji Kedelai Hasil Fermentasi dengan Aspergillus niger dalam Ransum terhadap Bobot Karkas Ayam Pedaging - Nelwida, Nelwida (Fakultas Peternakan Universitas Jambi, 2011)
The study was conducted to determine the effect of feeding fermented epidermis of soybean sedd with Aspergillus niger as substitution of maize and soybean meal in the ration on carcass weight of broiler . The study was carried out in Laboratory of Feed Science to analyze the nutrient content of feedstuffs and in the Cages under Laboratory of Poulty Nutrition, Faculty of Animal Science, University of Jambi for feeding trial. The experiment was designed to Completely Randomized Design (CRD) with 5 treatments and 4 replications. Feeding trial used 100 DOC starins MB-202 P fed basal ration with different level of fermented epidermis of soybean seed with Aspergillus niger as treatment. The treatments were R0 (basal ration without fermented epidermis of soybean seed with Aspergillus niger ), R1 (basal ration containing 10 % of fermented epidermis of soybean seed with Aspergillus niger), R2 (basal ration containing 20 % of fermented epidermis soybean seed with Aspergillus niger), R3 (basal ration containing 30 % of fermented epidermis soybean seed with Aspergillus niger) and R4 (basal ration containing 40 % of fermented epidermis soybean seed with Aspergillus niger). Parameters measured were feed consumption, body weight and carcass weight. Result of this study showed that substitution of maize and soybean meal with fermented epidermis of soybean seed using Aspergillus niger significantly (P<0,05) influenced feed consumption, body weight and absolute carcass weight but no significantlt (P>0,05) on percentage carcass weight of broiler. It is concluded that fermented epidermis of soybean seed with Aspergillus niger could be mixed in to the ration up to 40 % to substitute maize and soybean meal and it was not negative influenced on carcass weight of broiler.